Les Consequences - Toni, Servillo; Magnani,Olivia; Giannini, Adriano, 1971-; Ballero, Antonio, 1864-1932.; Gianna, Paola Scaffidi (Italy, 2004)
Titta di Girolamo apparently has a regular and tedious life with nothing strange a part from his own name (as he uses to say)...
Keywords: Drama